African Journal of Emergency Medicine Vol.5 Issue 2, 2015 - African Federation for Emergency Medicine (Elsevier, 2015)
-An unusual tourist. A case of a body packer's death in Botswana -Fascia iliaca compartment block in dislocated hip reduction -Assiting the setting up of an emergency service in rural africa